Pharmaceutical consumption in human and veterinary medicine in Germany: potential environmental challenges - Abdallah, Mies; Bethäuser, Jenny; Tettenborn, Felix; Hein, Arne; Hamann, Melanie (Frontiers in Environmental Science, 2024)
Pharmaceutical usage in both human and veterinary medicine contributes substantially to societal well-being. However, concerns regarding its environmental impacts are increasing. Despite global awareness, a substantial knowledge gap exists in Germany and several other countries regarding pharmaceutical residues, hindering comprehensive environmental risk assessments. This study aims to bridge this gap by analyzing veterinary pharmaceutical consumption in livestock farming in Germany and comparing it with human pharmaceutical usage, subsequently correlating these findings with environmental data on pharmaceutical residues to conduct a straightforward analysis of the environmental risk posed on non-target entities such as soil, water bodies, and microorganisms. Data from 129 agricultural farms in Germany were utilized to comprehensively analyze veterinary pharmaceutical usage. Extrapolation to national levels estimates a substantial quantity of active substances used, particularly antibiotics and electrolytes. Comparison with human pharmaceutical usage highlights differences in substance prevalence and usage patterns. Environmental correlations indicate a considerable presence of pharmaceutical residues in Germany, with notable distinctions between human and veterinary sources. In the environmental risk analysis, significant differences are evident between individual active substances within the same substance group. The study underscores the importance of addressing pharmaceutical residue impacts on the environment and emphasizes the necessity of comprehensive data for informed decision-making and environmental management strategies.